Sustained Virological Response by Direct Antiviral Agents in HCV Leads to an Early and Significant Improvement of Liver Fibrosis. Issue 2 (February 2018) - Persico, Marcello; Rosato, Valerio; Aglitti, Andrea; Precone, Davide; Corrado, Mariano; Luna, Antonio De; Morisco, Filomena; Camera, Silvia; Federico, Alessandro; Dallio, Marcello; Claar, Ernesto; Caporaso, Nicola; et al.
Background: Direct antiviral agents (DAA) demonstrated high efficacy among HCV-infected patients in registered trials. Nevertheless, the impact of these therapies on liver stiffness measurement (LSM) and liver functionality in 'real-life' is not well-known. The aim of the present study was to evaluate the sustained virological response (SVR) impact on LSM and clinical parameters of DAA-therapy on a real-life population of HCV patients with F3/F4 fibrosis. Methods: A total of 749 HCV genotype 1–4 patients with F3/F4 hepatitis undergoing antiviral therapy were consecutively enrolled in four centres of hepatology in Italy. Clinical, biochemical and imaging data were collected at the baseline (T0), at the end of treatment (EoT) and after 12 weeks (SVR12). Results: Out of 749 patients, 69.7% were F4 and 30.3% were F3. SVR12 was reached in 97.5%. LSM significantly decreased from T0 to EoT ( P <0.001), whereas, it did not from EoT to SVR12 ( P = not significant). Moreover, in F4 no significant differences were found in Child and MELD between T0, EoT and SVR12 ( P = not significant). At the univariate analysis of clinical and liver parameters, baseline high glucose ( P <0.005), type 2 diabetes ( P <0.001), low alanine aminotransferase (ALT; P <0.001), low platelets ( P <0.005), and the presence of esophageal varices (EV; P <0.001) were found to be associated with a lack of a significant EoT LSM improvement. At multiple regression, ALT ( P <0.05), diabetes ( P <0.005) and EV ( P <0.05) were inversely associated with significant LSM reduction. Conclusions: Virological response to DAA is associated with fibrosis regression and recovery of liver functionality and this can be detected as early as EoT. HCV eradication is associated with a rapid and significant clinical improvement that lasts over time and seems to be negatively influenced by diabetes and EV.